Pelatihan Cerdas Menabung dan Pencatatan Keuangan UMKM bagi Wirausaha Pemula di Kota Bandung - Solihin, Rici (Indonesian Journal for Social Responsibility, 2024)
One of the causes of failure among novice entrepreneurs in the first five years of running their businesses is the lack of successful financial management. The goal of the activity Community Service is to educate novice entrepreneurs to have good financial literacy by conducting Smart Saving and Financial Recording Training using Financial Recording Applications for MSMEs (Micro, Small, and Medium Enterprises). The implementation method of community service activities involves various activities such as lectures, discussions, case studies, and practical exercises like making envelopes packaged as games to make it more enjoyable for participants. Initially, novice entrepreneurs were unfamiliar with business bookkeeping and were not accustomed to saving and investing for their business development. However, after receiving training in business bookkeeping and smart saving, they were able to improve their business records using the SiApik application. Moreover, they began planning their business development by saving and investing.